Kaolin based ceramics obtained by Freeze casting process (2016)
(Eng) Freeze casting offers a tremendous opportunity to obtain bio-inspired synthetic materials that mimic microstructural characteristics of natural materials like bone and nacre. These natural materials display high strength and toughness; properties usually desired in synthetic engineering materials. The freeze casting process involves four basic steps. The ceramic slurry preparation consists of fine ceramic particles that are suspended in a fluid. In the current work, water based kaolin suspensions were prepared varying the volume fraction of ceramic particles. After the ceramic slurry is properly prepared, the slurry is frozen. The solidification process is often performed using directional freezing, which creates laminar pores, providing the microstructural characteristics of the final part. When a crystal is formed the frozen front moves the particles around it, allowing particles to agglomerate around the crystal, creating different types of pores. In the present study, freezing rates were varied. Subsequently, the samples have to be lyophilized in order to sublimate the frozen liquid phase. Sublimation is the transformation of a solid phase directly to the gas phase. As a result the lyophilized sample has a porous structure with a replica of the water crystals formed during freezing. As a final step, sintering of ceramics is performed. Results of the microstructural characteristics of the samples revealed that varying the volume fraction of ceramic particles and freezing rates have a direct influence on the pore characteristics, changing from circular to laminar pores.